2009
DOI: 10.1063/1.3080251
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the isotopic evolution of pressurized water reactor fuel using an antineutrino detector

Abstract: By operating an antineutrino detector of simple design during several fuel cycles, we have observed long term changes in antineutrino flux that result from the isotopic evolution of a commercial Pressurized Water Reactor (PWR). Measurements made with simple antineutrino detectors of this kind offer an alternative means for verifying fissile inventories at reactors, as part of International Atomic Energy Agency (IAEA) and other reactor safeguards regimes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 12 publications
2
41
0
Order By: Relevance
“…Previous experiments have demonstrated variations in the total reactor antineutrino flux with fuel evolution [17,18] while providing indications that a change in the spectral shape with fuel evolution may be present [18]. In this Letter, we report the direct observation of a change in the reactor antineutrino flux and spectrum with reactor fuel evolution.…”
mentioning
confidence: 63%
“…Previous experiments have demonstrated variations in the total reactor antineutrino flux with fuel evolution [17,18] while providing indications that a change in the spectral shape with fuel evolution may be present [18]. In this Letter, we report the direct observation of a change in the reactor antineutrino flux and spectrum with reactor fuel evolution.…”
mentioning
confidence: 63%
“…Additionally, the effects of misreported power shifts can give insight to the test's sensitivity to detector drifts. The detector used in this analysis has not been deployed long enough to study these effects, but the SONGS1 detector showed a less than 1% drift while taking data [21].…”
Section: B Rate Evolution Analysismentioning
confidence: 99%
“…Reactor monitoring withν e has been demonstrated using the inverse beta-decay reac- [72] tion [2,18]. In recent demonstrationsν e monitoring has been able to successfully monitor the isotopic evolution of fuel in a reactor, detect on-off status .…”
Section: Monitoring Of Nuclear Reactors For Nuclear Safeguardsmentioning
confidence: 99%